Study of knowledge management models and their relevance in organisations. (1st August 2019) - Mittal, Saurabh; Kumar, Vikas
Advances in the domain of information sharing and communication have generated huge volumes of data in last few decades. Data stored for the various business activities becomes important for performance measurement, corrections, modification, enhancement and venturing into other dimensions of business. Along with this data, there are various direct/indirect stakeholders having vast experience and great knowhow of the business processes, which may be critical to the business strategy. The modern information technology management tools have made it easy to manage and process the information from different sources which results in knowledge generation. The present work traverses the journey of knowledge management discipline from an organisational perspective considering the different levels of organisations. Prominent knowledge management models have been identified and a comparative analysis has been presented. Various knowledge management tools have been analysed to meet the needs of the modern businesses for management of information and generation of knowledge.